What do haematological cancer survivors want help with? A cross-sectional investigation of unmet supportive care needs - Hall, Alix E (BMC Res Notes, 2015)
BACKGROUND: This study aimed to identify the most prevalent unmet needs of haematological cancer survivors. METHODS: Haematological cancer survivors aged 18–80 years at time of recruitment were selected from four Australian state cancer registries. Survivors completed the Survivor Unmet Needs Survey. The most frequently reported “high/very high” unmet needs items were identified, as well as characteristics associated with the three most prevalent “high/very high” unmet needs reported by haematological cancer survivors. RESULTS: A total of 715 eligible survivors returned a completed survey. “Dealing with feeling tired” (17%), was the most frequently endorsed “high/very high” unmet need. Seven out of the ten most frequently endorsed unmet needs related to emotional health. Higher levels of psychological distress (e.g., anxiety, depression and stress) and indicators of financial burden as a result of cancer (e.g., having used up savings and trouble meeting day-to-day expenses due to cancer) were consistently identified as characteristics associated with the three most prevalent “high/very high” unmet needs. CONCLUSIONS: A minority of haematological cancer survivors endorsed a “high/very high” unmet need on individual items. Additional emotional support may be needed by a minority of survivors. Survivors reporting high levels of psychological distress or those who experience increased financial burden as a result of their cancer diagnosis may be at risk of experiencing the most prevalent “high/very high” unmet needs identified by this study.